Unlocking Sustainable Success in Saudi Arabia: The Interplay of Knowledge Management and Green Innovation - Alshammari, Khalid H. (Archives of Business Research, 2023)
As organizations around the world address sustainability issues, increasing attention is being devoted to the role that knowledge management can play in encouraging ecologically desirable behavior. The primary goal of the study was to evaluate how knowledge management affects sustainable performance, with an emphasis on the mediating function of green innovation. Data were acquired from 275 managers and senior employees working in the oil, gas, electricity, water desalination, and minerals industries in Saudi Arabia. The primary method of data collection was a self-administered and online survey. Using the Advanced Structural Equation Modeling (AMOS) tool, the data were assessed, and a thorough examination of the connections between knowledge management, green innovation, and sustainable performance was created. According to the results, there is a direct link between knowledge management and sustained performance. Furthermore, it was discovered that green innovation acted as a mediating component in this relationship, shedding light on the advantages that knowledge management brought to green innovation and how those advantages benefitted sustainable performance. This study adds to the body of current literature by empirically proving the linkages between knowledge management, green innovation, and sustainable performance. It emphasizes how important knowledge management is in promoting environmentally friendly behaviors and provides practical advice for companies trying to match their strategy with sustainability goals.